2009
DOI: 10.1016/j.jhazmat.2009.02.119
|View full text |Cite
|
Sign up to set email alerts
|

Performance of fuel cell using calcium phosphate hydrogel membrane prepared from waste incineration fly ash and chicken bone powder

Abstract: Waste incineration fly ash and bone powder could be successfully recycled to calcium phosphate hydrogel, a type of fast proton conductor. The electric conductivity of the crystallized hydrogel from them was compared with that from calcium carbonate reagent. It was found that the conductivity of the hydrogel from bone powder is almost equal to that from calcium carbonate reagent, which is higher than that from incineration fly ash. Because the crystallized hydrogel from incineration ash has a lower crystallinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The X‐ray diffraction (XRD) analysis of the bone powder shows crystalline phase of Ca 10 (PO4) 6 (OH) 2 (JCPDS No. :74–0566) . The XRD pattern corresponding to the Cu/bone nanocomposite is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The X‐ray diffraction (XRD) analysis of the bone powder shows crystalline phase of Ca 10 (PO4) 6 (OH) 2 (JCPDS No. :74–0566) . The XRD pattern corresponding to the Cu/bone nanocomposite is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…There is a significant volume of research related to the use of fly ash as a filler or binding element in the formation of polymer hydrogels. From these studies, it can be concluded that hydrogels containing fly ash exhibit significant mechanical stability and rheological advantages compared to conventional hydrogels [30,31,32]. This indicates that fly ash can be a useful addition to hydrogels.…”
Section: The Application Of Fly Ash In Various Areas Of the Oil And G...mentioning
confidence: 90%
“…One of the most famous water-absorbing materials is hydrogel, which is a cross-linked polymer with high water absorption property that yet maintains a well-defined structure in water. It has been applied in water purification treatment, , electrode materials, , fuel cells, etc. For example, chitosan and poly­(vinyl alcohol) (PVA) hydrogel binders with high water retention properties were conducive to ion migration in direct borohydride fuel cells at high operating temperatures .…”
Section: Introductionmentioning
confidence: 99%